Analysis of the Sum Minimization Possibilities of Heat Exchanger Core Masses in Internal Combustion Engine Cooling Systems - Yuryi Moshentsev; Oleksiy Gogorenko; Olha Dvirna; Andrzej Kubit (Applied Sciences, 2023)
Rational designs for cooling systems (CS) of internal combustion engines are formulated in the form of a series of circulation circuits. The engine is integrated into a circuit with the highest and unregulated flow of internal circuit coolant (ICC). All heat exchangers are placed in circulation circuits with relatively reduced and adjustable ICC flow rates. While the circuits are usually interconnected, they can also be designed to operate independently. This CS scheme enables the achievement of the minimum possible value of the sum of masses of exchanger cores, denoted as MΣ. The reduction in MΣ is achieved through the regulation of ICC flow in a closed circulation loop involving two heat exchangers. The variations in MΣ based on the circuit parameters have been thoroughly investigated. The reduction in MΣ can also be applicable to more intricate systems. A decrease in MΣ, under identical initial CS parameters, may occur in different magnitudes, depending on the specific features of the CS scheme and the operating conditions of the heat exchangers within it. Cooling systems, constructed with the same initial parameters and comprising multiple circulation circuits that meet all criteria for rational design, may exhibit diverse configurations. Examples of such systems are explored, and the minimum values of MΣ are calculated for each. It has been determined that the disparity in the minimum values of MΣ for such systems, while maintaining equal efficiency, can exceed 30%. The selection of the optimal CS scheme is contingent not only on achieving the minimum possible value of MΣ but also on various other factors.